2022
DOI: 10.29413/abs.2022-7.5-1.9
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the general condition and quality of life of women of post-reproductive age after asymptomatic COVID-19 and 12 months after moderate COVID-19

Abstract: The aim. To assess the general condition, laboratory parameters, quality of life of women of post-reproductive age after asymptomatic COVID-19 and 12 months after moderate COVID-19.   Material and methods. We examined 47 women (45–69 years old), divided into 3 groups: those who did not have COVID-19, not vaccinated (group 1 – control; n = 15); women 12 months after moderate COVID-19, accompanied by pneumonia (group 2; n = 19); women with IgG in their blood who deny any symptoms of COVID-19 (group 3; n = 13).  … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 19 publications
1
1
0
Order By: Relevance
“…The results of an earlier study assessing life quality indicators in patients without COVID-19 clinical symptoms showed no differences with controls, however, scores for physical condition were higher in asymptomatic patients. Also, elevated high-density lipoprotein cholesterol level was noted as compared to control values [2]. These results and the present study data suggest the presence of a more advanced antioxidant system, better functioning of organs and systems, and a more adapted to respiratory virus infection immune system in patients who have asymptomatic COVID-19.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…The results of an earlier study assessing life quality indicators in patients without COVID-19 clinical symptoms showed no differences with controls, however, scores for physical condition were higher in asymptomatic patients. Also, elevated high-density lipoprotein cholesterol level was noted as compared to control values [2]. These results and the present study data suggest the presence of a more advanced antioxidant system, better functioning of organs and systems, and a more adapted to respiratory virus infection immune system in patients who have asymptomatic COVID-19.…”
Section: Discussionsupporting
confidence: 75%
“…During menopause, women begin to experience agerelated neuroendocrine changes, accompanied by estrogen deficiency, which is considered as a condition for higher vulnerability to moderate and severe COVID-19 and subsequent complications [1]. It has been shown that menopausal women even 1 year after COVID-19, experience physical and emotional health problems, which may be due to endothelial dysfunction [2,3]. One of the mechanisms for the development of endothelial dysfunction is oxidative stress that develops during SARS-CoV-2 virus infection [4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%